Biochemical characterization of a novel carboxypeptidase inhibitor from a variety of Andean potatoes. (December 2015) - Lufrano, Daniela; Cotabarren, Juliana; Garcia-Pardo, Javier; Fernandez-Alvarez, Roberto; Tort, Olivia; Tanco, Sebastián; Avilés, Francesc Xavier; Lorenzo, Julia; Obregón, Walter D.
Graphical abstract: Cloning, recombinant expression, biochemical and kinectic characterization of a proteinaceous inhibitor of metallocarboxypeptidases, A/B subfamily, from a variety of Andean potatoes. Highlights: Isolation of proteinaceous inhibitor of metallocarboxypeptidases, A/B subfamily, from potato. Natural divergences of amino acid residues that constitute the secondary binding site in PCI-like inhibitors. Importance of secondary binding site in formation of the complex enzyme-inhibitor. Abstract: Natural protease inhibitors of metallocarboxypeptidases are rarely reported. In this work, the cloning, expression and characterization of a proteinaceous inhibitor of the A/B-type metallocarboxypeptidases, naturally occurring in tubers of Solanum tuberosum, subsp . andigenum cv. Imilla morada, are described. The obtained cDNA encoded a polypeptide of 80 residues, which displayed the features of metallocarboxypeptidase inhibitor precursors from the Potato Carboxypeptidase Inhibitor (PCI) family. The mature polypeptide (39 residues) was named imaPCI and in comparison with the prototype molecule of the family (PCI from S. tuberosum subsp. tuberosum ), its sequence showed one difference at its N-terminus and another three located at the secondary binding site, a region described to contribute to the stabilization of the complex inhibitor-target enzyme. In order to gain insights into the relevance of the secondary binding site in nature, a recombinant form of imaPCI (rimaPCI) having only differences at the secondary binding site with respect to recombinant PCI (rPCI) was cloned and expressed in Escherichia coli . The rimaPCI exhibited a molecular mass of 4234.8 Da by MALDI-TOF/MS. It displayed potent inhibitory activity towards A/B-type carboxypeptidases (with a K i in the nanomolar range), albeit 2–4-fold lower inhibitory capacity compared to its counterpart rPCI. This result is in agreement with our bioinformatic analysis, which showed that the main interaction established between the secondary binding site of rPCI and the bovine carboxypeptidase A is likely lost in the case of rimaPCI. These observations reinforce the importance of the secondary binding site of PCI-family members on inhibitory effects towards A/B-type metallocarboxypeptidases. Furthermore, as a simple proof of concept of its applicability in biotechnology and biomedicine, the ability of rimaPCI to protect human epidermal growth factor from C-terminal cleavage and inactivation by carboxypeptidases A and B was demonstrated.